2010
DOI: 10.1186/1423-0127-17-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Taurine in health and diseases: consistent evidence from experimental and epidemiological studies

Abstract: Taurine (T) was first noted as beneficial for stroke and cardiovascular diseases (CVD) prevention in genetic rat models, stroke-prone spontaneously hypertensive rats (SHRSP). The preventive mechanisms of T were ascribed to sympathetic modulation for reducing blood pressure (BP) and anti-inflammatory action. Recent epidemiological surveys revealed the involvement of inflammatory mediators in the pathogenesis of stroke and also atherosclerosis for which T was proven to be effective experimentally. Arterio-lipido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 52 publications
4
88
0
7
Order By: Relevance
“…12 Several clinical studies have reported that diets rich in taurine can reduce cardiovascular risks regardless of ethnicity and genetic background. 13,14 In addition, animal experiments have shown that taurine depletion accelerates the development of high salt-induced hypertension. 15 Although taurine has been shown to lower blood pressure (BP) in several hypertensive animal models, few rigorous and long-term clinical trials have confirmed this beneficial effect in human hypertension.…”
mentioning
confidence: 99%
“…12 Several clinical studies have reported that diets rich in taurine can reduce cardiovascular risks regardless of ethnicity and genetic background. 13,14 In addition, animal experiments have shown that taurine depletion accelerates the development of high salt-induced hypertension. 15 Although taurine has been shown to lower blood pressure (BP) in several hypertensive animal models, few rigorous and long-term clinical trials have confirmed this beneficial effect in human hypertension.…”
mentioning
confidence: 99%
“…Epidemiological studies have shown that increased taurine intake is associated with diminished risk of hypertension (Yamori et al 2010). This observation is consistent with animal studies showing taurine-mediated reductions in blood pressure of spontaneously hypertensive rats (Nara et al 1978), attenuation of norepinephrinemediated vasoconstriction by taurine (Nishida and Satoh 2009) and elevation in blood pressure in taurine deficiency (Mozaffari et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fujita et al [155] demonstrated a reduction in BP of 9/4.1 mmHg (p < 0.05) in 19 hypertension subjects given 6 g of taurine for 7 d. Taurine has numerous beneficial effects on the cardiovascular system and BP [156] . The recommended dose of taurine is 2 to 3 g/d at which no adverse effects are noted, but higher doses up to 6 g/d may be needed to reduce BP significantly [1,70,71,[154][155][156][157][158][159][160][161][162] .…”
Section: Proteinmentioning
confidence: 99%
“…Taurine lowers BP, SVR and HR, decreases arrhythmias, CHF symptoms and SNS activity, increases urinary sodium and water excretion, increases atrial natriuretic factor, improves insulin resistance, increases NO and improves endothelial function. Taurine also decreases A-Ⅱ, PRA, aldosterone, SNS activity, plasma norepinephrine, plasma and urinary epinephrine, lowers homocysteine, improves insulin sensitivity, kinins and acetyl choline responsiveness, decreases intracellular calcium and sodium, lowers response to beta receptors and has antioxidant, anti-atherosclerotic and anti-inflammatory activities, decreases IMT and arterial stiffness and may protect from risk of CHD [1,[154][155][156][157][158][159][160] . A lower urinary taurine is associated with increased risk of hypertension and CVD [160,161] .…”
Section: Proteinmentioning
confidence: 99%